Seed germination performances of Styrax species help understand their distribution in Cerrado areas in Brazil - Kissmann, Camila [UNESP]; Habermann, Gustavo [UNESP] (Inst Agronomico, 2013)
In this descriptive paper, we described germination responses of Styrax pohlii, S. camporum and S. ferrugineus seeds at 5, 10, 15, 20, 25, 30, 35, 40 and 45 degrees C. We also assessed the percentage germination (% G) of S. pohlii seeds with different seed water contents because, as a forest species, it seems to have recalcitrant seed behavior. Intrigued by the capacity of seeds of this species to germinate directly from puddles formed on poorly drained soils of riparian forests, where it typically occurs, we also tested the effect of de-pulping fruits on germination of S. pohlii seeds under hypoxia and normoxia conditions. In addition, we checked whether distinct concentrations of gibberellic acid (GA(3)) could break S. ferrugineus seed dormancy, a typical seed behavior of Cerrado species. No germination occurred at 5, 40 and 45 degrees C, regardless of the species. The optimal temperature for germination was 20 degrees C for S. pohlii and 25 degrees C for S. camporum. However, S. ferrugineus seeds showed a very low % G, regardless of the temperature, and GA(3) could not consistently break possible physiological seed dormancy. For S. pohlii seeds, the higher the seed desiccation the lower the % G, and fruit pulp removal showed to be essential for seed germination. S. pohlii seeds germinated independently of oxygenation conditions.
Keywords: hypoxia; Styrax pohlii; S. camporum; S. ferrugineus; temperature; desiccation seed tolerance